Land Inequality, Education, and Marriage: Empirical Evidence from Nineteenth-Century Prussia - Francesco Cinnirella; Erik Hornung (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this study we review the literature on the relationship between landownership inequality and the accumulation of human capital in historical perspective. Furthermore we provide new evidence on the relationship between landownership inequality and marriage patterns at the county level in nineteenth-century Prussia. Formally the landed elite could have inuenced not only the labor relations with the peasants but also their marriage decisions. Using cross-sectional as well as panel analysis we find no evidence that noble landowners directly affected marriage rates. Instead we find a robust negative association between average formal education and the share of married women. This finding is in line with recent theoretical and empirical literature on the role of gender specific human capital in the demographic transition.
Keywords: O43; Q15; I25; J12; N33; 330; land inequality; education; marriage; Prussian economic history